PENGARUH METODE OUTDOOR LEARNING TERHADAP PEMBENTUKAN KARAKTER CURIOSITY DAN RESPONSIBILITY DI SD ALAM AL-IZZAH KRIAN SIDOARJO - Purwantiningsih, Budi; Putri, Bunga Alfiani (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract The low curiosity of students there are still those who are silent and do not ask questions and the responsibilities of students who are still doing assignments not on time and not active in group work, are expected to raise the character of curiosity and responsibility. Therefore the research emphasizes the formation of Curiosity (curiosity) and Responsibility (responsibility) characters in students through the application of the Outdoor Learning method. The purpose of this research is to find out whether there is an influence of outdoor learning methods on the character of curiosity and responsibility at SD Alam Al-Izzah Krian Sidoarjo. This type of research is quantitative using observation techniques, documentation and questionnaires. The data obtained were analyzed using the percentage formula and simple linear regression analysis. The results of this study indicate that 1) The formation of curiosity and responsibility characters is said to be well known from the percentage of 91.2%. 2) There is an effect of the outdoor learning method on the character of curiosity, this is based on calculations from simple linear regression with a significance value of 0.044 <0.05 and a tcount value of 2100 > table 2040 so it can be concluded that the outdoor learning method has an effect on the character of curiosity. And 3) There is an influence of the outdoor learning method on the character of responsibility, this is based on calculations from simple linear regression, it can be obtained a significance value of 0.018 < 0.05 and a tcount of 2.499 > ttable 2.040 so it can be concluded that the outdoor learning method has an effect on responsibility.